2008
DOI: 10.1016/j.otohns.2008.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting functional rhinoplasty or nasal valve repair: A 25‐year systematic review

Abstract: There is substantial level 4 evidence to support the efficacy of modern-day rhinoplasty techniques for treatment of nasal obstruction due to nasal valve collapse. More recent studies have incorporated validated patient-reported outcome measures, with more rigorous statistical analysis. Future study design improvements include the use of comparison cohorts and incorporating standardized objective outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 45 publications
2
133
0
2
Order By: Relevance
“…61 Techniques such as static and dynamic inspection, the modified Cottle maneuver (as depicted in Figure 5), 62 and palpation can augment the physical examination. 60,[63][64][65] Furthermore, the rhinoplasty surgeon should be cognizant of the dynamic nature of the operation and consider how attempts to alter the aesthetic appearance of the nose may affect nasal airway obstruction. For example, careful evaluation of the strength of the nasal tip and lower lateral cartilages is important, as too much resection in the setting of weak cartilage can lead to postoperative nasal obstruction.…”
Section: Supporting Textmentioning
confidence: 99%
“…61 Techniques such as static and dynamic inspection, the modified Cottle maneuver (as depicted in Figure 5), 62 and palpation can augment the physical examination. 60,[63][64][65] Furthermore, the rhinoplasty surgeon should be cognizant of the dynamic nature of the operation and consider how attempts to alter the aesthetic appearance of the nose may affect nasal airway obstruction. For example, careful evaluation of the strength of the nasal tip and lower lateral cartilages is important, as too much resection in the setting of weak cartilage can lead to postoperative nasal obstruction.…”
Section: Supporting Textmentioning
confidence: 99%
“…They have not been included in almost all the evaluations done so far and they make the relevancy of the research difficult. Anyway, significant respiratory pathological conditions and abnormalities were not frequent in our research [17,18].…”
Section: Discussionmentioning
confidence: 47%
“…As a result, much of our knowledge in nasal valve surgery is based on retrospective reports. That being said, both Rhee et al [59] and Spielmann et al [10] found that despite the lack of level I data, there is good evidence that nasal valve surgery is beneficial for patients. In 2010, Rhee et al [6] proposed guidelines for treatment of nasal valve collapse based on available literature and expert consensus.…”
Section: Discussion/ebmmentioning
confidence: 99%